Education on Stroke Prevention for the Elderly in Gampong Bada, Ingin Jaya District, Aceh Besar - Nanda Desreza; Rizkidawati Rizkidawati; Edy Cahyady; Siti Aisyah Nisvi (CV. Proaksara Global Transeduka, 2024)
Stroke is a condition characterized by rapidly developing clinical signs of focal and global neurological deficits, which may worsen and last for 24 hours or more, potentially leading to death. The purpose of this activity is to enhance the community's understanding of stroke prevention to avoid its complications. This activity was carried out in Bada Village, Aceh Besar. The participants who attended in person were 18 residents of Bada Village. The method of this community service activity was conducted in the form of counseling and discussion.The event took place on August 14, 2024, starting at 09:30 AM until it concluded. The activity began by registering the participants, followed by an explanation of the event's objectives and material related to stroke, its causes, and complications. From the event, it was found that the community's understanding of poor dietary habits (low in fiber), low physical activity, and excessive salt use in cooking was lacking. Hence, it is recommended for those at risk to improve their lifestyle, eating habits, and rest patterns, and for families to continuously provide strong motivation to family members who are already at risk.